Armazenamento óptico reversível em filmes guest-host contendo compostos azoaromáticos em forma de V dispersos em uma matriz de polimetilmetacrilato - Silva, Lidiana Maranesi (2019)
In the materials science and engineering’s field we can highlight the important role of polymer materials that have been used in the development of several technologies such as light emitting organic diodes, 2D and 3D optical storage devices, coating materials and thin films. In addition, insulating polymers with interesting mechanical properties have been studied as host matrices of chromophores for optical purposes. Among these, we can highlight the polymethylmethacrylate and its technological applications in optical devices that will be the focus of this study. In this context, the main goal of this project is the development of an optical information storage device from a guest-host film, it has no chemical bond between the chromophore and the host matrix, of a V-shaped azoaromatic chromophore (YB3p25/YB3p91). In order to do this device, it is necessary to use a polymeric host matrix for the chromophore that allows its alignment in a region of the space and at the same time does not lose the recorded information. The polymer films contain azoaromatic compounds (DR13 (standard material) and a compound to be evaluated) in the form of a guest-host film for high molecular alignment after storage. The information recording takes place by photoisomerization (isomerization of the molecule using the energy provided by the light source), in this way the chromophores tend to be aligned perpendicularly to the direction of the electric field of the incident radiation, increasing the refraction index in this direction (optical birefringence). The birefringence was induced by a continuous linearly polarized green diode laser (532 nm) with variable intensity and a second low intensity HeNe (632,8 nm) laser will be used as a reading device. Thus, it was possible to obtain a residual memory for the film containing DR13 a value of (10.1 ± 0.1) %, the typicals values of this type of film. For YB3p91, the value obtained was (50.8 ± 0.1) % and (49.2 ± 0.1) % were obtained for YB3p25, values ​​ above those found in the literature for guest-host type films.